Investigating the Role of Metoclopramide and Hyoscine-N-Butyl Bromide in Colon Motility - Omar, Sleman Y.; Mamand, Dyari M.; Omer, Rebaz A.; Rashid, Rzgar F.; Salih, Musher I. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
Metoclopramide is a treatment for gastroenteritis accompanied by vomiting. Hyoscine-n-butyl bromide as an anticholinergic agent causes inhibition of the acetylcholine (Ach) by acting on muscarinic receptors. The study aims to ascertain how metoclopramide affects Ach-induced cortical motility and also investigates the effects of metoclopramide alone and in combination with hyoscine-n-butyl bromide drug effects on colon motility. In this study, 1 cm of colon tissue width was cut, 2 cm long strips were made, and both sides of the tissue were secured with surgical silk at both ends of isolated bath tissues of isolated organs with (1g) tension to the suspended instrument that recorded isometric contractions. Tissue fixation is followed by drug addiction: Ach, metoclopramide, and hyoscine-N-butyl bromide. The tissue was treated with metoclopramide and hyoscine-n-butyl bromide and excess Caine for 10 min. The results show changes in colon frequency, peak-to-peak, and amplitude levels for metoclopramide, hyoscine-N-butyl, and metoclopramide and hyoscine. Apaired T-test statistically analyzes the results. Metoclopramide by itself, as well as in combination with hyoscine-n-butyl bromide, increases colon motility and induces Ach release. In addition, an analysis of the physicochemical characteristics of hyoscine-n-butyl bromide and metoclopramide molecules is conducted. The study includes theoretical calculations of electronic parameters for both protonated and unprotonated forms of these molecules in both gaseous and aqueous environments. These results show the potential use of metoclopramide as a therapeutic option for gastroenteritis with vomiting, warranting additional study, and clinical evaluation. The research also reveals hyoscine-n-butyl bromide and metoclopramide’s molecular features by their physicochemical properties.